2019
DOI: 10.1186/s12964-019-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

The let-7 family of microRNAs suppresses immune evasion in head and neck squamous cell carcinoma by promoting PD-L1 degradation

Abstract: Background: Accumulation of immunosuppressive protein programmed death-ligand 1 (PD-L1) has been documented in several cancers and contributes to the evasion of the host immune system. However, cancer cellintrinsic signaling-dependent control of PD-L1 expression remains to be elucidated. Herein, we aimed to identify the let-7 family of microRNAs as candidates that up-regulate tumor cell PD-L1 expression and mediates immune evasion of head and neck squamous cell carcinoma (HNSCC). Methods: The expression of let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Several studies have shown that PD-1/PD-L1 pathway has become a potential therapeutic target for a wide range of human malignancies [28][29][30][31][32][33]. However, the associations between expression of PD-L1 and clinico-pathological parameters are not consistent [18,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that PD-1/PD-L1 pathway has become a potential therapeutic target for a wide range of human malignancies [28][29][30][31][32][33]. However, the associations between expression of PD-L1 and clinico-pathological parameters are not consistent [18,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Let-7a/b can inhibit PD-L1 glycosylation and promote PD-L1 degradation in HNSCC, and the process is achieved via the β-catenin/STT3 pathway 103 . EMT can induce the N-glycosyltransferase STT3 through β-catenin transcription, stabilize the N-glycosylation of PD-L1 and increase its expression, finally helping CSCs escape from the immune system 104 .…”
Section: Glycosylation-related Immune Checkpoints and Hnscc Immune Esmentioning
confidence: 99%
“…The combination led to the most profound reduction in tumor mass. Analysis of the tumor samples revealed that the combination led to marked CD8+ T cell infiltration and profound IFN-γ production in tumor-infiltrating lymphocytes indicating enhanced immune activity and a potential synergism [ 97 ]. These results indicate that the let-7 family of miRNAs has potent activity in the microenvironment by shifting immune cells towards an antitumor phenotype often required for successful ICI treatment.…”
Section: Mirnas As Therapeutic Adjuvant For Immune-checkpoint Inhimentioning
confidence: 99%